#### Answer

-2x-y=-1

#### Work Step by Step

(-2;5),(-6;13)
m=$\frac{13-5}{-6+2}$=$\frac{8}{-4}$=-2
slope - 2 , through (-2;5)
y-$y_{1}$=m(x-$x_{1}$)
y-5=-2(x+2)
-5=-2x-4-y
-5+4=-2x-y
-1=-2x-y
-2x-y=-1

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

-2x-y=-1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.